Об одном алгоритме ε-субградиентного типа минимизации выпуклой функции - Журбенко, Н.Г.; Ненахов, Э.И. (Теорія оптимальних рішень, 2004)
An algorithm of constructing two cutting planes localizing the set of solutions to the problem of convex function e-minimum. This algorithm provides for as small as needed angle between cutting planes. It is based on the procedure of one-dimensional descent. The results of numerical experiments are given.